The Spanish Citrus Industry - Navarro, Luis (2017)
The Spanish citrus industry has a long and worldwide known tradition. Citrons (Citrus medica) were introduced by the Romans during the V century, sour oranges (C. aurantium), lemons (C. limon), and pummelos (C. maxima) by the Arabs during the X and XI centuries, sweet oranges (C. sinensis) by Genoese traders during the XV century and a reintroduction of higher quality varieties by the Portuguese in the XVI century and finally, the mandarins (C. reticulata) during the XIX century. Initially citrus were used as ornamental plants and for medicinal purposes, and after the introduction of sweet oranges also for direct consumption at very local scale. Commercial plantings started at the end of the XVIII century and exports of fresh fruit to other European countries were done from this time. Today the Spain has 330.000 ha producing 6.3 million tons. About 50% of the production is exported as fresh fruit, 20% is consumed in the internal market also as fresh fruit, 18% is processed and the rest are wastes. Spain is the fifth production country and the first fresh fruit citrus exporting country in the world.